Benin - Decentralized City Management - Mohan, P.C. (World Bank, Washington, DC, 2012)
The objective of the First Decentralized City Management project - 2000-2004 (credit equivalent of US$25.5 million) was to provide better quality and more cost-effective basic services to urban residents, especially the poor, of Benin's 3 main cities - Cotonou, Porto- Novo and Parakou. The project was the first phase of a planned 2-phase Adaptable Program Loan (APL) and followed a previously successful project, the Urban Rehabilitation and Management project.